A study of flame and flow development with hydrous and anhydrous fuels in an optical spark ignition engine - Moslemin Koupaie, Mohammadmohsen (2019)
The work reported in this thesis was concerned with improving understanding of the in-cylinder flow and combustion with future fuels in a modern spark ignition engine, including hydrous ethanol as a potentially attractive solution in future dedicated ethanol IC engines. The experiments were performed in a single cylinder optical research engine equipped with a modern central direct injection combustion chamber and Bowditch style optical piston. Results were obtained under “typical” part-load engine operating conditions with ethanol, iso-octane, B16I84, E10I90, E6B8I85, E85I10W5 and hydrous ethanol at 5%, 12% and 20% volume water. High speed cross-correlated particle image velocimetry was undertaken at 1500rpm motoring conditions with the intake plenum pressure set to 0.5 bar absolute and the horizontal imaging plane fixed 10mm below the combustion chamber “fireface”. Comparisons were made to CFD computations of the flow. Complimentary flame images were obtained via natural light (chemiluminescence) over multiple engine cycles. The flame images revealed the tendency of all fuels flame to migrate towards the hotter exhaust side of the combustion chamber, with no complimentary bulk air motion apparent in this area in the imaging plane. This exhaust migration phenomenon has been noted previously by others in optical pent-roofed engines but without both flow and flame imaging data being available. The faster burning ethanol offset the tendency of the flame to migrate towards the hotter exhaust walls. The fastest combustion rate occurred with pure ethanol, with higher water content (>5%) generally slowing down the flame speed rate and offsetting the flame speed/migration benefit (in good agreement with recent laminar burning velocity correlations for hydrous ethanol).